Correction: Kwon-Chung, K.J. et al. Is Cryptococcus gattii a Primary Pathogen? J. Fungi 2015, 1, 154–167 - Kyung J. Kwon-Chung; Tomomi Saijo (Journal of Fungi, 2016)
The authors of the published paper [1] would like to correct Table 1.[...]